AN INTEGRATIVE MODEL FOR STRENGTHENING PKBM SUSTAINABILITY THROUGH SERVANT LEADERSHIP, ORGANIZATIONAL CLIMATE, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, AND TRAINING EFFECTIVENESS BASED ON SITOREM - Suyadi Suyadi; Bibin Rubini; Dian Wulandari (Taksasila Edukasi Insani, 2026)
PKBM Sustainability is an important issue in strengthening non-formal education because Community Learning Centers (PKBM) play a role in expanding access to education, supporting lifelong learning, and fulfilling community needs. This study aims to develop a model and strategy for improving PKBM Sustainability by examining the effects of servant leadership, organizational climate, Organizational Citizenship Behavior (OCB), and the effectiveness of education and training. The study employed a combination of simple qualitative and quantitative methods involving 39 PKBM in 7 subdistricts in eastern Bogor Regency, with a population of 279 respondents and a sample of 165 respondents. Data were analyzed using path analysis and SITOREM. The results show that servant leadership, organizational climate, OCB, and the effectiveness of education and training have positive and highly significant effects on PKBM Sustainability. In addition, servant leadership and organizational climate also have indirect effects on PKBM Sustainability through OCB and the effectiveness of education and training. The SITOREM analysis recommends several priority indicators for improvement, namely the availability of teaching staff, PKBM development, fulfillment of community needs, empowerment, conceptualization, work mechanisms, tolerance, courtesy, and satisfaction with activities. Therefore, PKBM Sustainability can be strengthened through an integrative model based on servant leadership, organizational climate, organizational citizenship behavior, the effectiveness of education and training, and SITOREM-based indicator optimization.Keywords: PKBM Sustainability; servant leadership; organizational climate; OCB; effectiveness of education and training; SITOREM.